The Utility of Point of Care Test for Soluble ST2 in Predicting Adverse Cardiac Events during Acute Care of ST-Segment Elevation Myocardial Infarction - Anggoro Budi Hartopo; Indah Sukmasari; Ira Puspitawati (Cardiology Research and Practice)
Introduction. Soluble ST2 (sST2) is increased during acute myocardial infarction. The point of care test (POCT) for sST2 is currently available. The aim of this study was to investigate the utility of the sST2 POCT measurement for predicting adverse cardiac events during acute care of ST-elevation myocardial infarction (STEMI). Patients and Methods. This research used a cohort study design. Consecutive patients with STEMI were enrolled. Soluble ST2 level was measured from peripheral blood taken on admission with POCT. Observation during acute intensive care was conducted to record adverse cardiac events. Two groups were assigned based on median sST2 level, that is, supramedian and inframedian group. The incidence of adverse cardiac events between groups was analyzed. A p value < 0.05 was statistically significant. Results. We analyzed 95 subjects with STEMI and 10 patients with stable coronary artery disease as controls. The median sST2 level was significantly higher in subjects with STEMI as compared to controls (152.1 ng/mL versus 28.5 ng/mL, p<0.01). Among subjects with STEMI, the supramedian group had higher incidence of adverse cardiac events than the inframedian group (38.3% versus 12.5%, p=0.004). Multivariable analysis showed that supramedian sST2 level was independently associated with increased incidence of adverse cardiac events (adjusted OR 6.27; 95% CI: 1.33–29.47, p=0.020). Conclusions. The sST2 POCT measurement was useful to independently predict adverse cardiac events during acute intensive care of STEMI.